Role of Information in SMEs Supporting Services on Business Performance in South Korea. (November 2017) - Park, Hun; Kwon, Tae-Hoon; Jang, Tae-Jong; Yoo, Jae-Young; Lee, Ho-Shin; Moon, Seong-Hee; Hahn, Hyuk
The research objective of our study is to find the route how the information provided in small- and medium-sized enterprise (SME) supporting services in South Korea affects business performances. Investigation into business performances from SME supporting services was conducted by a survey method. The survey data was statistically analysed by using SPSS program. A research model was designed by using a mediation model. In our research model, information utilisation of SME supporting services was selected as an independent variable; contribution degree to decision-making, growth of information competitiveness and customer satisfaction were introduced as mediating variables; and SME business performances, such as contribution degree to growth of current revenue, future revenue, future export and current employment, were used as dependent variables. Correlation and regression were analysed to investigate the relationship between two variables such as independent variables versus mediating variables, independent variables versus dependent variables and mediating variables versus dependent variables. The route from information provision in SME supporting services to business performances was clarified by using Baron and Kenny's mediation model.